OK. Here's my generalization
which ran into some resistance
when posted as a separate problem.
Let $f(x)$ be such that
$f(1) = 1,
f'(x) > 0, f''(x) < 0,
f(x) \to \infty,
n \in \mathbb{N}
\implies f^{(-1)}(n)\in \mathbb{N}
$.
($f^{(-1)}(n)$
is the inverse function of $f$)
What can we say about
$$S=\sum_{k=1}^{\infty} \dfrac{(-1)^{k+1}}{\lfloor f(k) \rfloor} $$
Let $g$ be the
inverse function of $f$,
so
$f(g(x)) = g(f(x)) = x
$.
Let
$u(n) =
\begin{cases}
0 \text{ if } n \text{ odd}\\
1 \text{ if } n \text{ even}\\
\end{cases}
=\dfrac{(-1)^n+1}{2}.
$
\begin{align}
S
&=\sum_{k=1}^{\infty} \dfrac{(-1)^{k+1}}{\lfloor f(k) \rfloor}\\
&=\sum_{n=1}^{\infty} \sum_{k=g(n)}^{g(n+1)-1} \dfrac{(-1)^{k+1}}{\lfloor f(k) \rfloor}\\
&=\sum_{n=1}^{\infty} \sum_{k=g(n)}^{g(n+1)-1} \dfrac{(-1)^{k+1}}{\lfloor n \rfloor}\\
&=\sum_{n=1}^{\infty} \dfrac1{n}\sum_{k=g(n)}^{g(n+1)-1} (-1)^{k+1}\\
&=\sum_{n=1}^{\infty} \dfrac1{n}\sum_{k=0}^{g(n+1)-g(n)-1} (-1)^{k+g(n)+1}\\
&=\sum_{n=1}^{\infty} \dfrac{(-1)^{g(n)+1}}{n}\sum_{k=0}^{g(n+1)-g(n)-1} (-1)^{k}\\
&=\sum_{n=1}^{\infty} \dfrac{(-1)^{g(n)+1}}{n}u(g(n+1)-g(n)-1)\\
\end{align}
If $f(k) = \sqrt{k}$,
then
$g(n) = n^2$
so
$u(g(n+1)-g(n)-1)
=u(2n)
=1
$
and
$(-1)^{g(n)+1}
=(-1)^{n^2+1}
=(-1)^{n+1}
$
so
$$S
=\sum_{n=1}^{\infty} \dfrac{(-1)^{g(n)+1}}{n}u(g(n+1)-g(n)-1)
=\sum_{n=1}^{\infty} \dfrac{(-1)^{n+1}}{n}
=\ln(2).
$$
If $f(k) = \sqrt[3]{k}$,
then
$g(n) = n^3$
so
$u(g(n+1)-g(n)-1)
=u(3n^2+3n)
=u(3n(n+1))
=1
$
and
$(-1)^{g(n)+1}
=(-1)^{n^3+1}
=(-1)^{n+1}
$
so
$$S
=\sum_{n=1}^{\infty} \dfrac{(-1)^{g(n)+1}}{n}u(g(n+1)-g(n)-1)
=\sum_{n=1}^{\infty} \dfrac{(-1)^{n+1}}{n}
=\ln(2).
$$
If $f(k) = \sqrt[m]{k}$,
then
$g(n) = n^m$
so
$\begin{array}\\
u(g(n+1)-g(n)-1)
&=u((n+1)^m-n^m-1)\\
&=u(\sum_{j=1}^{m-1} \binom{m}{j}n^j)\\
&=u(\sum_{j=1}^{\lfloor \frac{m-1}{2} \rfloor} (\binom{m}{j}n^j+\binom{m}{m-j}n^{m-j})
\qquad\text{central binomial coefficient is even}\\
&=u(\sum_{j=1}^{\lfloor \frac{m-1}{2} \rfloor} (\binom{m}{j}(n^j+n^{m-j}))\\
&=u(\sum_{j=1}^{\lfloor \frac{m-1}{2} \rfloor} (\binom{m}{j}n^j(1+n^{m-2j}))\\
&=1
\qquad\text{since }n^j(1+n^{m-2j})
\text{ is even}\\
\end{array}
$
and
$(-1)^{g(n)+1}
=(-1)^{n^m+1}
=(-1)^{n+1}
$
so
$$S
=\sum_{n=1}^{\infty} \dfrac{(-1)^{g(n)+1}}{n}u(g(n+1)-g(n)-1)
=\sum_{n=1}^{\infty} \dfrac{(-1)^{n+1}}{n}
=\ln(2)
$$